2016
DOI: 10.15537/smj.2016.4.14833
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of teaching automated external defibrillators use using a traditional classroom instruction versus self-instruction video in non-critical care nurses

Abstract: Objectives:To evaluate the effectiveness and retention of learning automated external defibrillator (AED) usage taught through a traditional classroom instruction (TCI) method versus a novel self instructed video (SIV) technique in non-critical care nurses (NCCN).Methods:A prospective single-blind randomized study was conducted over 7 months (April-October 2014) at the Universiti Kebangsaan Malaysia Medical Center, Kuala Lampur, Malaysia. Eighty nurses were randomized into either TCI or SIV instructional techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 16 publications
(17 reference statements)
0
34
0
Order By: Relevance
“…Other authors concur that the knowledge level on critical skills deteriorates gradually within 6 months. 12 , 13 Nurses’ knowledge levels have also been noted to be influenced by their motivation, attitude and willingness to learn BLS or participate in drills. 14…”
Section: Discussionmentioning
confidence: 99%
“…Other authors concur that the knowledge level on critical skills deteriorates gradually within 6 months. 12 , 13 Nurses’ knowledge levels have also been noted to be influenced by their motivation, attitude and willingness to learn BLS or participate in drills. 14…”
Section: Discussionmentioning
confidence: 99%
“…improve the technical competencies and the knowledge retention. [23][24][25][26][27][28][29] The sociodemographic analysis showed that these two groups were significantly different in terms of age, educational background, and experience in CPR. Reasonably, the medical group would have an enormous gap in KAP compared to the non-medical group.…”
Section: Discussionmentioning
confidence: 99%
“…This additional mode of teaching deliveries can increase the depth of understanding, improve the technical competencies and the knowledge retention. 2329…”
Section: Discussionmentioning
confidence: 99%
“…Through the study of the effectiveness of teaching, it can be found that the effectiveness of teaching thinking has gradually shaped. In order to achieve the expected teaching objectives, teachers will influence students through routine teaching behavior in the interaction between teachers and students, so that students can obtain satisfactory learning results [7].…”
Section: State Of the Artmentioning
confidence: 99%